Atopy, asthma, and risk of bladder cancer: Systematic review and meta-analysis of cohort studies - Suoyi Feng; Ziqi Shao; Longzhu Ju; Yiting Zhang (European Journal of Inflammation, 2021)
The relationship between atopic diseases and cancer at various sites has been extensively studied. Previous epidemiological studies have investigated the association between atopic diseases and bladder cancer; however, the results remain inconclusive. In this study, we performed a systematic review and meta-analysis of cohort studies published thus far to evaluate the association between atopy and the risk of bladder cancer. We conducted a systematic search in PubMed, Embase, ISI Web of Science, and Scopus to identify potentially relevant studies. The pooled risk ratio (RRs) and 95% confidence intervals (95% CIs) were calculated using a random-effect model considering the heterogeneity among studies. On the basis of our selection criteria, a total of 10 cohort studies were included in our meta-analysis involving 2,341,005 participants, of whom 1720 were patients with bladder cancer. The pooled RR of bladder cancer in the group with atopic disease versus the group without atopic disease was 1.31 (95% CI: 1.10–1.56, p  < 0.01), indicating a positive association between overall atopy and bladder cancer risk. In subgroup analysis, the pooled RR of bladder cancer was 1.46 (95% CI: 1.18–1.80, p  < 0.001) for asthma and 1.03 (95% CI: 0.74–1.44, p  = 0.86) for allergic rhinitis. The risk of bladder cancer is positively associated with overall atopy and asthma, but is not associated with allergic rhinitis.